HUBUNGAN ANTARA INTENSITAS PENDIDIKAN AGAMA ISLAM DALAM KELUARGA DENGAN PRESTASI BELAJAR SISWA KELAS VII SMP NEGERI 18 TANGERANG - Lia Nurkomariah; Ismail Marzuki (Universitas Muhammadiyah Tangerang, 2022)
ABSTRAKThis study was conducted to determine (1) the intensity of Islamic religious education in the family, (2) to determine the learning achievement of students' Islamic religious education. (3) To find out whether there is a relationship between the intensity of Islamic religious education and the learning achievement of class VII students of SMP Negeri 18 Tangerang. This research was conducted at SMP Negeri 18 Tangerang. The research method used is a survey method which leads to hypothesis testing. The population in this study was class VII students who found 107 students, with a sample of 84 students, having been tested for validity and reliability. A total of 20 questions about the intensity of Islamic religious education in the family and learning achievement of Islamic religious education. Based on careful calculations, the value of r_(count )= 3,424. These results are then consulted with r_(table ) both at the 5% significance level for the two-tailed test and df = n-2 or 84-2 = 82, if r_(count) > r_(table) then it is significant. From hypothesis testing, it is obtained that r_(table ) is 0.2146 with it being said that t_(count )> t_(table ) (3.424 > 0.2146). In conclusion, there is a relationship between the intensity of Islamic religious education in the family with Islamic religious education learning for seventh grade students of SMP Negeri 18 Tangerang